The Effect of Employee Motivation on Organizational Performance At the Regional Development Planning Agency (Bappeda) Banyuwangi and Jember Regency - Giyanto, Giyanto; Rasaili, Wilda; Fitriyah, Nina Sa’idah; Aini, Dini Noor; Hasanah, Usrotul; Susanto , Hari (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
This study aims to analyze the influence of Employee Motivation on Organizational Performance at the Regional Development Planning Board (Bappeda) of Banyuwangi and Jember Regencies. This study uses a quantitative descriptive research method. The population and sample amounted to 98 respondents consisting of all employees of the Regional Development Planning Agency of Banyuwangi Regency and Jember Regency. The instrument and data analysis technique used in this study is Partial Least Square (PLS). For data collection techniques using questions (questionnaires) or questionnaires distributed to all respondents.There are five indicators in the employee motivation variable used in this study, namely: 1) physical needs, 2) needs for security and safety, 3) social needs, 4) self-esteem needs, and 5) self-actualization. For organizational performance variables, there are six indicators used in research, namely 1) effectiveness, 2) efficiency, 3) quality, 4) productivity, 5) quality of work life, 6) learning and innovation. The results of this study indicate that employee motivation has a significant effect on organizational performance in the Regional Development Planning Agency (Bappeda) of Banyuwangi and Jember Regencies.